PENGARUH GOOD CORPORATE GOVERNANCE & KINERJA KEUANGAN TERHADAP NILAI PERUSAHAAN DI MASA PANDEMI COVID-19 - Lembayung, Haritra Dyah; Titisari, Kartika Hendra; Masitoh, Endang (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2022)
This study aims to determine and analyze the effect of good corporate governance and financial performance on firm value. The dependent variable in this study is firm value. While the independent variables used in this study are managerial ownership, audit committee size and, financial performance. The population of this study is the consumer goods industry sector companies listed on the Indonesia Stock Exchange (IDX) for the 2019-2020 period. The sample in this study used a purposive sampling method with certain criteria to obtain a sample of 53 companies in the consumer goods industry sector listed on the Indonesia Stock Exchange (IDX) for the 2019-2020 period. The data used is secondary data sourced from the annual report. The data analysis technique used multiple linear regression analysis. The results showed that managerial ownership and financial performance affected firm value. Meanwhile, the size of the audit committee has no effect on the value of the company in the consumer goods industry sector for the 2019-2020 period